BIOSORPSI ION LOGAM Cd (II) DARI LARUTAN MENGGUNAKAN KULIT BUAH PINANG - Lazulva, Lazulva; Utami, Lisa (Sainstek : Jurnal Sains dan Teknologi, 2017)
The ability of betel nut skin as a biosorbent at a low cost to remove the metal ions Cd (II) from the solution has been investigated. This study shows the effect of pH of the solution, contact time and initial concentration on the absorption capacity of betel nut skin. The result of measurement of metal ion content of Cd (II) using AAS shows that optimum pH of biosorption is 6 and the optimum contact time is 15 minutes, while the optimum initial concentration of biosorption is 50 ppm. Based on FTIR spectroscopic spectra, it can be concluded that the functional groups which act as binding metal ions Cd (II) by betel nut skin as biosorbent are amine function group (N-H), alcohol (O-H) and carbonyl (C = O). The result of the langmuir isotherm obtained by the price of Q (maximum absorption) for metal Cd is 1.14 mg / g.